Faktor-faktor yang Mempengaruhi Pengeluaran ASI pada Ibu Postpartum Di Wilayah Kerja Puskesmas Tanjung Agung Kecamatan Tanjung Agung Kabupaten Muara Enim Tahun 2021 - Rahmawati Ekaputri; Syarifah Ismed; Eka Afrika (Jurnal Ilmiah Universitas Batanghari Jambi, 2022)
Mother's milk contains a lot of colostrum which is rich in antibodies because it has protein content that is useful as an immune system that is useful for killing germs in large numbers so that giving breast milk can reduce the risk of infant death. This study used an analytic survey with a cross sectional research design. This research was conducted in the working area of the Tanjung Agung Public Health Center, Tanjung Agung District, Muara Enim Regency in August 2021. The population in this study were all postpartum mothers in the Tanjung Agung Health Center work area. The sample used amounted to 72 of the population taken by using the technique of determining the sample. Data analysis used univariate analysis (proportion) and bivariate analysis (Chi square test). The results of the analysis showed that diet, mother's knowledge, and nipple problems had a significant relationship with breastfeeding in postpartum mothers. The conclusion of this study is that there is a relationship between diet, knowledge of breast care and nipple problems simultaneously with breastfeeding in postpartum mothers in the Tanjung Agung Public Health Center, Tanjung Agung District, Muara Enim Regency in 2021. As a research suggestion, researchers hope that breastfeeding mothers can know what factors can affect milk production. so that the coverage of exclusive breastfeeding for infants continues to increase.